Growth of Highly (100)‐Oriented SrTiO3 Thin Films on Si(111) Substrates Without Buffer Layer. Issue 5 (1st April 2014) - Panomsuwan, Gasidit; Takai, Osamu; Saito, Nagahiro; Brennecka, G. L.
<x xml:space="preserve">Abstract</x> The SrTiO3 (STO) thin films were directly grown on Si(111) substrates without buffer layer by an electron‐cyclotron‐resonance ion beam sputter deposition. The growth temperature was varied from 700°C to 850°C, while other parameters were kept unchanged. X‐ray structural analysis demonstrates that the growth temperature has a strong influence in tuning degree of (100) orientation. The STO film grown at 800°C is found to be the highest degree of (100) orientation (98%) and a strong (100) fiber texture. For the surface morphology, the development of plate‐shaped grains reveals a good correlation with the change in the degree of (100) orientation. Moreover, the leakage current–voltage characteristics of the Au/STO/Si(111) metal‐insulator‐semiconductor capacitors are investigated and discussed in considerable detail.